치과의료관광에 대한 인식과 활성화 방안 - 최유리; Yu Ri Choi; 장선옥; Sun Ok Jang; 조윤정; Yoon Jeong Cho; 심연수; Youn Soo Shim (Han'guk Ch'iwisaeng Hakhoe chi, 2015)
Objectives: The purpose of the study is to investigate the awareness and activation towards dental medical tourism. Methods: A self-reported questionnaire was completed by 195 dental hygienists in Seoul from January 30 to September 15, 2014. Data were analyzed by one way ANOVA, chi square and t test using SPSS 19.0 program. the questionnaire consisted of general characteristics of the subjects, awareness towards medical tourism, medical tourism related hospitals, activation of Korean medical tourism, fields of medical tourism, and improvement of medical tourism. The questionnaire was adapted and modified from Kim and Kim by Likert scale. Results: Dental hygienists gave the high perception and possibility towards medical tourism (94.1%). Those carrying out medical tourism accounted for 39.5 percent. The most difficult problem was communication with foreigners (80.5%). The performance of prosthesis and anesthesia was the most specialized area that supported the medical tourism (84.1%). In order to improve the medical tourism implementation, dental medical technology must be strengthened (39.8%). Conclusion: The desirable dental medical tourism must be carried out by proficient dental medical manpower, higher technology, active participation and financial support by the government. This dental medical tourism will provide job opening for the dental hygienists.